An approach of image staganography by combine application of DNA sequence and arithmetic encoding - Chakraborty, Suman; K. Bandyopadhyay, Prof. Samir (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
In this paper an attempt has been made to hide an image with in a cover image by using DNA sequence and Arithmetic encoding.DNA sequence used to represent an image and arithmetic encoding convert this DNA sequence in decimal form within the range of 0 to 1.In this procedure encoding has been done in 2 level, 1st Secret-Image converted into decimal form and 2nd decimal form to DNA sequence. So, in this approach secret information is hidden in more depth. Increase depth provides more degree of security from external attack.